Rock collection paintings - Cameron, Mikie, author; Sullivan, Patrice, advisor; Emami, Sanam, committee member; Flippen, Paul, committee member; McKee, Patrick, committee member; Moseman, Eleanor, committee member (Colorado State University. Libraries, 2013)
Simply observing the world around me can be fascinating. Patterns and forms I find on stones and pebbles especially provoke my imagination. In my works, I observe and render natural forms onto surfaces; I interpret rocks from my collection into multi-colored, multi-layered, quiet paintings on carefully prepared panels. By translating my experience of these objects into art I am investigating my own perception of such an other, the alien rock - what it means to enter into a dialogue with it, subsequently constituting it and reconciling myself with it. Following this activity, a painting is created; an entirely new thing is made that the viewer can then contemplate. What follows is a description of how my work relates to contemporary theoretical considerations of perception, phenomenology, and epistemology. The rock collection paintings are a visual exploration of theoretical notions including phenomenology of perception, play transformed into structure, and experience of the other. As a result of the process of experiencing and translating a rock into a quiet oil painting I produce a visual playground. What exists is not two closed off subjects: the painting and the viewer, but a playful yet serious dialogue occurring between the two entities. What emerges from the discourse between viewer and painting is a form of self-knowledge. These works of art are forms of truth that, in part, shape the viewer.
Keywords: oil painting; rocks; phenomenology; painting; perception; abstraction